Urban water crisis and the promise of infrastructure: a case study of Shimla, India - Sarkar, Soma (Frontiers in Water, 2023)
Urban water configurations evolve through synergetic relationships that are non-linear, spatially variable, and temporally contingent. As urban development grows in complexity, dense water flow networks intensify within the urban landscape and pose a major challenge to urban water governance. At this junction, this study takes up the specific case study of the water crisis in Shimla, a city situated in the Western Himalayas, which was once the summer capital of British India. Shimla witnessed two significant episodes of a severe water crisis in 2016 and 2018, respectively. While the mainstream discourses identified erratic rainfall due to climate change, urban growth, and tourism as the prime causes, the crisis was not marked by absolute scarcity. Multitude configurations of infrastructure politics, distribution, and access produced scarcity, which differentially impacted the people in the city and continues to do so. Marginalized social groups (class, caste, gender, and religion) and people living on the periphery, such as slum dwellers, daily wage laborers, and informal sector workers with inadequate economic and social safety nets seem to have been missing from the discourse. In addition, the crisis events in Shimla have led to institutional changes in the governance of water by establishing a parastatal body for a water utility in the city and the proposal of mega water infrastructure projects for the bulk supply of water from the Sutlej River. Deriving from a situated urban political ecology approach, this study presents an in-depth empirical understanding of the complex urban waterscape of Shimla city, where the tourism industry is a major stakeholder, and a critical analysis of the emerging “new” politics of water, which is also a politics of infrastructure in Shimla's post-crisis phase. It adopts a qualitative research design involving in-depth interviews with different stakeholders in urban water governance in Shimla and a neighborhood-level case study to understand the post-crisis water scenario in the city. Locating the Shimla case study within the broader planetary geography, this study argues that the water crisis, as a context, is dialectical. Despite the implementation of several hydraulic projects and the financialization of nature, the inherent fissures of inequality within the city that cause differential access to water remain.